UkrVO Astronomical WEB Services - Mazhaev, A. (Наука та інновації, 2017)
Ukraine Virtual Observatory (UkrVO) has been a member of the International Virtual Observatory Alliance (IVOA) since 2011. The virtual observatory (VO) is not a magic solution to all problems of data storing and processing, but it provides certain standards for building infrastructure of astronomical data center. The astronomical databases help data mining and offer to users an easy access to observation metadata, images within celestial sphere and results of image processing. The astronomical web services (AWS) of UkrVO give to users handy tools for data selection from large astronomical catalogues for a relatively small region of interest in the sky. Examples of the AWS usage are showed. Українська віртуальна обсерваторія (УкрВО) є учасником Міжнародного альянсу віртуальних обсерваторій від 2011 року. Віртуальна обсерваторія не може вирішити всі проблеми зберігання і обробки даних, але вона надає користувачам стандарти для побудови інфраструктури астрономічних центрів даних. Астрономічні бази даних спрощують пошук даних і дають можливість вільного доступу до метаданих спостережень, зображень небесної сфери і результатів їх обробки та можливість зручного пошуку даних у великих астрономічних каталогах для відносно невеликої області на небесній сфері. Наведені приклади використання АВС. Украинская виртуальная обсерватория (УкрВО) участвует в работе Международного альянса виртуальных обсерваторий с 2011 года. Виртуальная обсерватория не может решить все проблемы хранения и обработки данных, но она предоставляет пользователям стандарты для построения инфраструктуры астрономических центров данных. Астрономические базы данных упрощают поиск данных и дают возможность свободного доступа к метаданным наблюдений, изображениям небесной сферы и результатам их обработки и легко выбрать данные из больших астрономических каталогов для относительно небольшой области на небесной сфере. Приведены примеры использования АВС.